Regulations of Retinal Inflammation: Focusing on Müller Glia - Chen, Yingying; Xia, Qinghong; Zeng, Yue; Zhang, Yun; Zhang, Meixia (Frontiers in Cell and Developmental Biology, 2022)
Retinal inflammation underlies multiple prevalent retinal diseases. While microglia are one of the most studied cell types regarding retinal inflammation, growing evidence shows that Müller glia play critical roles in the regulation of retinal inflammation. Müller glia express various receptors for cytokines and release cytokines to regulate inflammation. Müller glia are part of the blood-retinal barrier and interact with microglia in the inflammatory responses. The unique metabolic features of Müller glia in the retina makes them vital for retinal homeostasis maintenance, regulating retinal inflammation by lipid metabolism, purine metabolism, iron metabolism, trophic factors, and antioxidants. miRNAs in Müller glia regulate inflammatory responses via different mechanisms and potentially regulate retinal regeneration. Novel therapies are explored targeting Müller glia for inflammatory retinal diseases treatment. Here we review new findings regarding the roles of Müller glia in retinal inflammation and discuss the related novel therapies for retinal diseases.